Dmitrichenko N.F., Dovgal A.G., Bilyakovych O.N., Pruymak L.B., Sudorenko O.Y., Turitsa Y.A. Modelling of tribological characteristics of protective coating for power plants aviation ground equipment parts. - Дмитриченко, М.Ф.; Довгаль, А.Г.; Білякович, О.М.; Приймак, Л.Б.; Сидоренко, О.Ю.; Туриця, Ю.О. (Problems of Tribology, 2017)
On the basis of analysis of the compound conditions groove piston - piston ring was conducted planning for full factorial experiment two factors most affect the tribological characteristics of the message and the aluminum alloy specimens were tested as protective coatings with and without them. On the basis of the experimental data was carried out construction of the second order polinomonalnoi regression model for the friction characteristics of the coating, and the resulting image depending allow to predict the behavior of tribological coatings data at any point of the factor space. Key words: aircraft ground support equipment, power plant, protective coating, tribological characteristics, mathematical model, polynomial mpdel.